A new monozoic tapeworm, Lobulovarium longiovatum n. g., n. sp. (Cestoda: Caryophyllidea), from barbs Puntius spp. (Teleostei: Cyprinidae) in the Indomalayan region - Oros, Mikuláš; Ash, Anirban; Brabec, Jan; Kar, Pradip Kumar; Scholz, Tomáš (Systematic parasitology, 2012)
A new caryophyllidean cestode is described from barbs Puntius spp. (Cypriniformes: Cyprinidae), with P. sophore (Hamilton) as its type-host, in the Ganges and Brahmaputra river basins in India and Bangladesh, and a new genus, Lobulovarium n. g., is proposed to accommodate it. The genus belongs to the Lytocestidae because its vitelline follicles are situated in the cortex. It is typified by: (i) a peculiar ovary, which is roughly H-shaped, but with asymmetrical, irregular lobes on its ventral and dorsal sides; (ii) an extensive vitellarium formed by numerous vitelline follicles scattered throughout the cortex; (iii) a long, conical postovarian part of the body with numerous vitelline follicles; (iv) a broadly digitate scolex with a slightly protrusible central cone; (v) a single gonopore (male and female genital ducts open via a single pore and a common genital atrium is absent); and (vi) a small number of testes (< 60). Molecular data (partial sequences of the lsrDNA) indicate that Lobulovarium longiovatum n. sp. belongs among the most basal caryophyllidean cestodes, being unrelated to species from siluriform catfishes in the Indomalayan region. Paracaryophyllaeus osteobramensis (Gupta & Sinha, 1984) Hafeezullah, 1993 (syn. Pliovitellaria osteobramensis Gupta & Sinha, 1984) from another cyprinid fish, Osteobrama cotio (Hamilton), in Uttar Pradesh, India, is tentatively transferred to Lobulovarium as L. osteobramense (Gupta & Sinha, 1984) n. comb. It differs from L. longiovatum by having much smaller eggs (length <50 μm versus >90 μm in L. longiovatum), which are spherical (length/width ratio 1:1 versus 2.5-3:1 in the new species), and the presence of vitelline follicles alongside the ovarian lobes (almost completely absent in L. longiovatum).
Keywords: Bangladéš; nemoci ryb; Cestode Infections; Indie; druhová specificita; Fish Diseases; Female; zvířata; sladká voda; ženské pohlaví; Male; Fresh Water; cestodózy; Species Specificity; India; Animals; Bangladesh; mužské pohlaví; Cestoda; Cyprinidae